Recherche collatérale : rôles et enjeux des traces écrites dans l’accompagnement d’équipes d’écoles primaires - Martine Janner Raimondi (Recherches en Éducation)
Accompany research with teachers while the accompanists have exercised functions of adviser and training officer demands a big alertness to avoid amalgam positions and disturbance of research pruposes. If the choice of a collaborative research needs helping us to identify the purpose of actor’s empowerment and an ethical research position, it remained to find how make concrete this double aim. The written traces realize by both members of the research binomial and sent systematically to the actors before every debate, appeared necessary, not only to put our involvement with hindsight and favour cogitation but also self-defining trajectory of their community of practice. This communication, wich is founded on an international research ECOS of three years, aims to identify the characteristics of written traces leaves to surround in what they could play a role and that on the side of accompanists as on the side of accompanying. This cogitation leans against the experience of the accompaniment with three schools during two years. This article analyse stakes and impacts of writings provided during the first two meetings. It will be illustrated by extracts with one of these schools.